Mapping the Evolution of Blended Learning in Higher Education: A Bibliometric Analysis of English Language Proficiency Research - Chano, Jiraporn; Bonk, Curtis J.; Mohamad, Bahtiar (Universitas Negeri Makassar, 2025)
This study examines the evolution of blended learning (BL) research in higher education, focusing on its impact on English language proficiency (ELP) and alignment with Sustainable Development Goals. Using 200 Scopus-indexed articles published from 2020 to 2025, we applied Publish or Perish and VOSviewer for bibliometric analysis. Results show a pandemic-driven research surge, followed by a decline as institutions adapted. Thematic gaps emerged in the underuse of AI and gamification in ELP contexts. Geographic disparities were also evident, with minimal contributions from Global South regions. These patterns occurred because structural inequities limit digital access and research capacity in under-resourced areas. This analysis contributes by identifying emerging research priorities, supporting inclusive blended learning policies, and promoting South-South collaboration. The study has implications for advancing equitable and data-informed language education practices within hybrid learning models in alignment with Sustainable Development Goals (SDGs), especially SDG 4 (Quality Education) and SDG 10 (Reduced Inequalities).